Pelatihan Pengenalan Teknologi Digital Bagi Pengelola Masjid, Kecamatan Gajahmungkur Semarang - Murdowo, Sugeng; Khasanah, Fata Nidaul; Arifin, Wafi (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
The advancement of digital technology has brought significant changes to various aspects of life, including the management of religious institutions such as mosques. Digital technology encompasses various computer-based and internet-based devices and systems that enable efficiency and effectiveness in communication, administration, and community services. In the context of mosque management, the implementation of digital technology can provide substantial benefits in supporting information dissemination and optimizing religious activities. In recent years, many mosques in Indonesia have begun adopting digital technology to enhance services for congregants. This demonstrates that digital technology can be an effective tool for managing mosques in a more modern and professional manner. Some technological implementations that have proven beneficial for mosques include social media as a platform for disseminating information related to mosque activities and important announcements, as well as live streaming of religious events to reach congregants who are unable to attend physically in study sessions or sermons. The implementation of this initiative aims to provide mosque administrators with greater digital literacy. The stages of execution include counseling, training, and mentoring. The results of the initiative indicate strong enthusiasm from participants regarding the presented materials, and evaluations show that 100% of the conveyed content was deemed beneficial for mosque administrators.